Characteristics of seismic strata in the southeast Zhoushan Archipelago (East China Sea) with emphasis on shallow gas - Bing Deng; Junbing Chen (Frontiers in Marine Science)
Based on high-resolution sub-bottom seismic profiles collected on the coast of the Zhoushan Archipelago in the East China Sea, the distribution and characteristics of shallow gas have been analyzed. The strata in the area were divided into three geological units: Holocene fine-grained neritic facies muddy strata, Late-Pleistocene coarse-grained fluvial or lacustrine facies sandy strata, and bedrock. The presence of shallow gas was evidenced by various acoustic indicators, including acoustic blanking, enhanced reflections, gas chimneys, bright spots, and small mounds. Shallow gas accumulations are observed through the Lower and Upper Holocene strata, presumably related to the degradation of organic matter buried in the Holocene deposits and sealed by soft muddy deposits. The presence of ultra-shallow gas-charged sediment sealed by fine-grained muddy sediment in coastal areas with frequent human disturbance suggests a high potential for sediment instability. Moreover, frequent upward gas migration signatures were found in the study area. These gas migration features mainly occur in nearshore areas where tidal disturbance and human activities are both active. We therefore deduced that the deduction of sediment above probably decreased the pressure, thereby resulting in increased upward migration. The presence of active shallow gas within thin, soft muddy strata, along with the strong tidal turbulence and human activities, indicates that the seafloor of the study area is vulnerable to sediment erosion, and shallow gas is easily released, posing a potential danger to the stability of marine engineering foundations. Since the Changjiang sediment supply has been decreasing over the past decades, it will inevitably lead to corresponding morphological adjustments in the study area, such as seafloor erosion. To what extent coastal erosion will release the buried shallow gas and lead to unpredictable consequences is worthy of our sustained attention.